Immunohistochemical investigation of suprabasin and spexin immunoreactivity in psoriasis vulgaris - Turkoglu, Adrian; Demir, Betul; Cicek, Demet; Kuloglu, Tuncay; Artas, Gokhan; Hancer, Serhat; Gural, Yunus (Springer, 2026)
Psoriasis vulgaris (PV) is a chronic inflammatory disease characterized by erythematous squamous plaques. This study aimed to evaluate the immunoreactivity of suprabasin and spexin in healthy skin and PV and investigate their possible role in the pathogenesis of PV. A total of 40 skin samples were used, 20 with PV and 20 controls. Skin samples of patients with other dermatological diseases, malignancy, diabetes mellitus, obesity, and history of systemic drug use were excluded from the study. Immunohistochemical analysis of suprabasin and spexin was performed in skin samples. The suprabasin histoscores of the patient group with PV were statistically significantly lower than the control group, and the spexin histoscores were statistically significantly higher than the control group (0.26 +/- 0.07, 0.87 +/- 0.17, 1.60 +/- 0.59, 0.32 +/- 0.09, respectively), (p < 0.001). The data from this study suggest that suprabasin, a biomarker for malignancies, may not be a suitable biomarker for benign proliferative psoriasis. Spexin may contribute to the pathogenesis of PV through various mechanisms among its known metabolic and inflammatory biological functions. Future studies may provide clearer information by correlating clinical data with samples taken from the lesional, perilesional, or healthy adjacent skin and serum of patients with PV.
Keywords: Psoriasis Vulgaris; Suprabasin; Spexin